Client Importance, Nonaudit Services, and Abnormal Accruals - Chung, Hyeesoo; Kallapur, Sanjay (The Accounting Review, 2003)
The economic theory of auditor independence (DeAngelo 1981b) suggests that auditors' incentives to compromise their independence are related to client importance. Using ratios of client fees and of nonaudit fees divided by the audit firm's U.S. revenues or a surrogate for the audit-practice-office revenues as measures of client importance, we investigate their association with Jones-model abnormal accruals. In a sample of 1,871 clients of Big 5 audit firms we do not find a statistically significant association between abnormal accruals and any of the client importance measures. Our theory development also suggests that auditor incentives to compromise independence should increase with the extent of client opportunities and incentives to manage earnings, and decrease with the strength of corporate governance and auditor expertise. We also do not find a statistically significant association between abnormal accruals and client importance in subsets of the samples partitioned by proxies for these factors.